Ultrasound in radioembolization induced liver disease (REILD) - Bohle, W.; Zoller, W. G. (Zeitschrift für Gastroenterologie, 2015)
Background: REILD (radioembolization-induced liver disease) is a rare complication after SIRT (selective internal radiotherapy) of the liver. The diagnosis is based on a combination of clinical signs and symptoms, laboratory values, and MRT findings. Data about sonographic signs associated with REILD are lacking. In this report, we describe sonographic changes in two female patients with REILD.Case reports: Patient 1: a 34-year-old woman with colorectal carcinoma liver metastasis. Two weeks after SIRT, the patient developed histology-proven REILD. Abdominal ultrasound revealed pronounced hepatomegaly, with inhomogeneous, slightly hyperechoic parenchyma without attenuation. The well-known metastasis could not be delineated easily. Liver veins were compressed, with ill defined borders, and flattened biphasic blood flow in duplex sonography. Signs of portal hypertension with ascites, and splenomegaly were present. A therapy with diuretics, heparin, steroids, and ursodesoxycholic acid was introduced, and the patient recovered. After seven weeks, the ascites had resolved, and the liver parenchyma returned to normal echogenicity. Furthermore, the metastases in both lobes were clearly visible again. The liver veins were well delineated, normal sized, with regular triphasic blood flow in duplex sonography, but splenomegaly persisted. Patient 2: a 58-year-old women with recurrent multifocal peripheral cholangiocarcioma. Abdominal ultrasound 5 weeks after SIRT revealed a slightly increased echogenicity of the liver. Liver veins showed slightly irregular borders with biphasic flow pattern. In contrast to patient no. 1, liver metastases could still be delineated easily. Ascites or splenomegaly were not present. Laboratory parameters and MRT findings were consistent with a diagnosis of mild REILD. Liver biopsy was not performed. No specific therapy was introduced. Five weeks later, the liver parenchyma became more homogeneous again, and the liver veins normalized with smooth vessel borders, but still flattened biphasic flow pattern.Conclusion: Transient hepatomegaly, with inhomogeneous hyperechoic parenchyma without attenuation, and compressed, ill delineated liver veins, with monophasic or flattened biphasic blood flow, are typical sonographic findings in REILD. In addition, common signs of portal hypertension can be present. Liver alterations and ascites resolve parallel with clinical improvement. Splenomegaly can persist.
Keywords: SIRT; REILD; Ultraschall; Lebererkrankungen; Duplexsonografie; portale Hypertension